2009
DOI: 10.1007/s00011-009-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes modulate peritoneal leukocyte recruitment in peritonitis

Abstract: These data suggest that T cells act to suppress leukocyte recruitment while B cells promote leukocyte recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…While the initial cells mediating the inflammation over the first 24 h consist primarily of neutrophils, macrophages predominate the peritoneal infiltrate after 3 days [25]. At later time points, T-cells and B-cells play important roles in the immune response, but are detected at lower levels [26]. Here, we used this model of thioglycollate-induced inflammation to evaluate the influence of NEC in suppressing a macrophage-mediated inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…While the initial cells mediating the inflammation over the first 24 h consist primarily of neutrophils, macrophages predominate the peritoneal infiltrate after 3 days [25]. At later time points, T-cells and B-cells play important roles in the immune response, but are detected at lower levels [26]. Here, we used this model of thioglycollate-induced inflammation to evaluate the influence of NEC in suppressing a macrophage-mediated inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we observed the influence of manual acupuncture on peritonitis. Peritonitis is defined as inflammation of the peritoneum, from any cause, that spreads throughout the abdomen and might involve many types of cells, including resident macrophages, which play a critically important role in the orchestration of neutrophil recruitment to the peritoneal cavity [9, 10]. Thus, for this purpose, we evaluated the effect of SP6 acupuncture on an experimental animal model of carrageenan-induced peritonitis and also investigated mechanisms responsible for its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…T cells would act to limit leukocyte recruitment with an absence of T cells facilitating increased PMN and monocyte/MΦ recruitment. B cells would play a role in promoting MΦ recruitment in the later phase of inflammation as both RAG-1 KO mice and µMT mice exhibited reduced monocyte/macrophage (MΦ) recruitment at late time points [14]. …”
Section: Lymphocytesmentioning
confidence: 99%